Implementation of Traditional Knowledge Protection of Enbal Processing - Theresia Nolda Agnes Narwadan; Muchtar Anshary Hamid Labetubun; Sabri Fataruba (Batulis Civil Law Review, 2024)
Introduction: Implementation and regulations governing the protection of traditional knowledge is still considered less effective.  The law is expected to be able to overcome various problems that arise related to the protection of traditional knowledge from the community, especially the Kei Islands community on enbal processing knowledge.